Utilization of Turi Leaf Flour in Feed (Sesbania grandiflora Pers.) on Growth of Black Nile Tilapia (Orechromis niloticus) - Firmani, Ummul; Cahyoko, Yudi; Mustikoweni, Mustikoweni (Aquacultura Indonesiana, 2015)
Critical factor for successful fish farming is feed. Feed should always be available and in accordance with the needs of farmed fish both in quality and quantity. Black nile tilapia are reared intensively, requires diet crumb size with protein content is not less than 30%. Diet made by the composition and nutritional value in accordance with the age of the fish. The purpose of this study was to find the optimum percentage of leaf meal turi in artificial feed on the growth of black nile tilapia’s weight about 6 g/fish. The treatment in this study was the addition of turi leaf flour in artificial feed at 0%, 3%, 6%, 9% and 12%. Fish stocking density is maintained with 1 fish/L water for 40 days in a plastic tub volume of 15 liters and given the aerator. Measurement the amount of feed consumed was calculated to determine the feed efficiency. Data were analyzed using ANOVA and then the differences between treatments were tested using Duncan's Multiple Range Test. The results showed the highest of daily specific growth rate and feed efficiency obtained in the treatment of feed containing turi leaf flour of 0-9% were respectively 1.66 to 1.57% and from 45.57 to 39.82%. Keywords : Black nile tilapia; Daily specific growth rate; Feed efficiency; Turi leaf flour